Perception of climate change and the adaptation strategies and capacities of the rice farmers in Kedah, Malaysia - Akhtar, Rulia; Masud, Muhammad Mehedi; Afroz, Rafia (SAGE, 2019)
This article attempts to understand the perception of the rice-growing farmers on the issue of climate change (CC) and identify their adaptive capacity (AC). A survey was conducted through structured questionnaires to understand farmers’ perception and adaptation strategies in response to changing climate and variability. The findings indicate that farmers are moderately adaptive to CC in the study area. The result also revealed that the main barriers are lack of funds and government support available information to CC. Farmers with higher AC can produce greater amount of rice. Rice producers should be enabled through improved extension services, government aid, such as grants, training for better level of adaptability, to help them achieve higher rice production.